Reliability of ultrasound measurement of abdominal muscles thickness in women with and without chronic non-specific low back pain - Mahnaz Abofazeli; Amir Masoud Arab; Noroldin Karimi; Enayat Bakhshi; Zahra Mosalanezhad; Mehri Sirous (Vesnu Publications, 2013)
-